2019
DOI: 10.15588/1607-3274-2019-4-20
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Collision Avoidance With Multiple Targets, Including Maneuvering Ones

Abstract: Context. There is considered the task of automatic collision avoidance with multiple targets, including maneuvering ones. The object of the research is the process of automatic collision avoidance with multiple targets, including maneuvering ones. The subject of research is the method and algorithms that implement the process of automatic collision avoidance from multiple targets, including maneuvering ones. Objective. The purpose of the article is development a method and algorithms for automatic collision av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…For example, in the general concept of COLREG it is indicated that the differences of two vessels are considered. This feature is also described in the works of S. Zinchenko [6][7] (Fig. 1).…”
supporting
confidence: 67%
“…For example, in the general concept of COLREG it is indicated that the differences of two vessels are considered. This feature is also described in the works of S. Zinchenko [6][7] (Fig. 1).…”
supporting
confidence: 67%
“…The quality of products or services is largely determined by the effectiveness of the quality management system at the enterprise and the proper organization of the production process. The quality management system, built in accordance with the principles of overall quality management, involves continuous improvement of the marketing activities of the enterprise, improving the quality of products and ensuring of the needs of all interested parties, both customers and producers, through the establishment of appropriate management in the enterprise [25][26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the analysis of experimental data is helpful enough with illustrating that more than 47 % of navigators get used to having the same sequence of actions/operations when performing typical maneuvers (i.e. mooring, diverging from the vessel and whatever) [28,29]. Although, despite mentioned above, the time intervals between the stages of actions (nodes of trajectories) as well as the total available energy ( ) E t are expressed in an individual capacity.…”
Section: Figure 6 Database Of Navigation Eventsmentioning
confidence: 99%
“…La base metodológica de la investigación organizada en el contexto del establecimiento de perspectivas temporales en la actividad profesional de especialistas en la esfera económica es el complejo metodológico aprobado con el uso de los instrumentos de psicodiagnóstico (Blynova et al, 2020b;Fernández-Rivas y Espada-Mateos, 2019;Moya et al, 2018;Popovych et al, 2020a;Shevchenko et al, 2020). Esta metodología ha sido aprobada por investigadores en el estudio de los trastornos de adaptación, ansiedad, innovación (Acevedo-Duque et al, 2020;Halian et al, 2020a;Varguillas y Bravo, 2020), así como en el estudio de las expectativas mentales en diversas actividades de los encuestados (Cruz, 2019;Nosov et al, 2020a;Romero-Argueta et al, 2020;Tsiuniak et al, 2020;Zinchenko et al, 2019;. Todas estas mediciones experimentales y empíricas son relevantes para las perspectivas temporales en las actividades profesionales de los especialistas económicos.…”
Section: Metodologíaunclassified